SWEETENERS IN THE AGE OF CIVILIZATION DISEASES – A REVIEW OF CURRENT KNOWLEDGE, CONSUMER TRENDS AND THE ROLE OF THE FITNESS INDUSTRY - Marcin Ciechański; Edyta Witkowska; Klaudia Wilk; Szymon Cholewiński; Bernadetta Wilk; Piotr Stachura; Piotr Rejman; Katarzyna Pszczoła; Katarzyna Jurkiewicz; Aleksandra Kasprzyk (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: The global rise in obesity, type 2 diabetes, and cardiovascular diseases has intensified the search for dietary strategies to reduce added sugar intake. Low-calorie sweeteners (LCS) have emerged as widely used sugar substitutes, promoted as healthier alternatives. Despite their growing popularity, the long-term health impacts and role of LCS in disease prevention and metabolic regulation remain controversial.Aim of the study: This review aims to critically analyze the relationship between the increased consumption of LCS and the prevalence of metabolic diseases. Additionally, it explores the influence of the fitness market on the promotion and acceptance of sweeteners and examines global consumption trends and market forecasts.Materials and methods: A comprehensive literature review was conducted using PubMed and Google Scholar, analyzing recent clinical trials, preclinical studies and researches. The selected studies focus on the metabolic effects of LCS, public health implications, consumer behavior, and market data regarding global sweetener consumption. Attention was given to both synthetic and natural LCS.Conclusions: Low-calorie sweeteners have become a central component in dietary interventions targeting metabolic health. While some studies support their use as a tool for reducing caloric intake and managing blood glucose levels, others suggest possible adverse metabolic effects. Their widespread adoption, amplified by fitness culture and industry marketing continues to drive global market expansion. Further longitudinal research is essential to assess their safety, efficacy, and role in chronic disease prevention.